Heart Failure With Improved Ejection Fraction: Clinical Characteristics, Correlates of Recovery, and Survival: Results From the Valsartan Heart Failure Trial - Florea, Viorel G.; Rector, Thomas S.; Anand, Inder S.; Cohn, Jay N. (Circulation. Heart failure, 2016)
Heart failure with recovered or improved ejection fraction (HFiEF) has been proposed as a new category of HF. Whether HFiEF is clinically distinct from HF with persistently reduced ejection fraction remains to be validated. Of the 5010 subjects enrolled in the Valsartan Heart Failure Trial (Val-HeFT), 3519 had a baseline left ventricular EF of <35% and a follow-up echocardiographic assessment of EF at 12 months. Of these, 321 (9.1%) patients who had a 12-month EF of >40% constituted the subgroup with HFiEF. EF improved from 28.7±5.6% to 46.5±5.6% in the subgroup with HFiEF and remained reduced (25.2±6.2% and 27.5±7.1%) in the subgroup with HF with reduced ejection fraction. The group with HFiEF had a less severe hemodynamic, biomarker, and neurohormonal profile, and it was treated with a more intense HF medication regimen. Subjects who had higher blood pressure and those treated with a β-blocker or randomized to valsartan had greater odds of being in the HFiEF group, whereas those with an ischemic pathogenesis, a more dilated left ventricle, and a detectable hs-troponin had lower odds of an improvement in EF. Recovery of the EF to >40% was associated with a better survival compared with persistently reduced EF. Our data support HFiEF as a stratum of HF with reduced ejection fraction with a more favorable outcome, which occurs in a minority of patients with HF with reduced ejection fraction who have a lower prevalence of ischemic heart disease, a less severe hemodynamic, biomarker, and neurohormonal profile, and who are treated with a more intense HF medication regimen. URL: http://www.clinicaltrials.gov. Unique identifier: NCT00336336.